1964
DOI: 10.1111/j.1537-2995.1964.tb02884.x
|View full text |Cite
|
Sign up to set email alerts
|

Simple Rapid Osmotic Fragility Test Proposed as a Routine in Blood Banks

Abstract: A rapid micromethod for recording red cell osmotic fragility by continuous decrease of salt concentration was used. It requires one drop of blood and it yields an automatically recorded curve and/or its derivative in less than ten minutes. The blood of 100 donors was tested on the day after donation. One case out of 100 showed an abnormal fragility curve. The deterioration of the blood during storage in ACD at 4 C. and the consequent modification of the fragility curve was followed. Marked individual variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1965
1965
2002
2002

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 12 publications
(6 reference statements)
1
7
0
Order By: Relevance
“…As demonstrated, the osmotic fragility did not present any significant alteration during the four weeks of storage. Based on the studies, which correlate curves of normal fragility to an adequate preservation and good viability of stored blood 13 , the present results reinforce the evidence that WR6026 does not interfere with the viability of the erythrocytes.…”
Section: Discussionsupporting
confidence: 85%
“…As demonstrated, the osmotic fragility did not present any significant alteration during the four weeks of storage. Based on the studies, which correlate curves of normal fragility to an adequate preservation and good viability of stored blood 13 , the present results reinforce the evidence that WR6026 does not interfere with the viability of the erythrocytes.…”
Section: Discussionsupporting
confidence: 85%
“…The usefulness of the instrument has been demonstrated in clinical diagnosis (Danon, Shiffman and Efrati, 1965) and in blood transfusion centres (Danon, Frei, Rimon and Ben David, 1964;Valeri, Mercado-Lugo and Danon, 1965). By measurement of osmotic fragility it is possible to assess deterioration of blood during storage.…”
Section: David Darzonmentioning
confidence: 99%
“…As shown by Danon and co-workers (1,2 ) , the automatically recorded osmotic fragility curve of blood or of its derivative ("fragiligrams") are quite different in normal fresh blood than in blood which has been stored for several weeks. David, Lustig and Nahas (3) also showed that the fragiligrams of blood sampled from patients with thalassemia major or with spherocytosis have a very abnormal shape.…”
mentioning
confidence: 97%